2019
DOI: 10.11118/actaun201967061433
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Acidification of Coconut Water Waste by Lactobacillus acidophilus Culture for Biotechnological Production of Lactic Acid

Abstract: The biotechnological production of lactic acid could be carried out via anaerobic acidification process. In order to achieve an optimal production of lactic acid, the role of inoculum would be essential. The current study aimed to investigate as well as evaluate the effect of inoculum concentration on the anaerobic acidification of coconut water waste for the production of lactic acid. Results showed that the addition of 20% inoculums to the reactor fermenting coconut water waste was sufficient for the optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Several studies have reported coffee fermentation employing specific microbes, such as yeasts (e.g., Saccharomyces cerevisiae), acetic acid bacteria (e.g., Acetobacter xylinum), and lactic acid bacteria (LAB) [22][23][24]. However, the use of a pure microbial culture may not significantly enhance the physicochemical properties of coffee, as it tends to alter a specific component to produce a particular fermentation end-product [25]. In contrast, mixed microbial cultures could potentially enhance the physicochemical characteristics of coffee [20] and promote the desired tastes and aroma [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported coffee fermentation employing specific microbes, such as yeasts (e.g., Saccharomyces cerevisiae), acetic acid bacteria (e.g., Acetobacter xylinum), and lactic acid bacteria (LAB) [22][23][24]. However, the use of a pure microbial culture may not significantly enhance the physicochemical properties of coffee, as it tends to alter a specific component to produce a particular fermentation end-product [25]. In contrast, mixed microbial cultures could potentially enhance the physicochemical characteristics of coffee [20] and promote the desired tastes and aroma [17].…”
Section: Introductionmentioning
confidence: 99%